CSGALNACT1‐congenital disorder of glycosylation: A mild skeletal dysplasia with advanced bone age. Issue 3 (3rd December 2019) - Mizumoto, Shuji; Janecke, Andreas R.; Sadeghpour, Azita; Povysil, Gundula; McDonald, Marie T.; Unger, Sheila; Greber‐Platzer, Susanne; Deak, Kristen L.; Katsanis, Nicholas; Superti‐Furga, Andrea; Sugahara, Kazuyuki; Davis, Erica E.; et al.
Abstract: Congenital disorders of glycosylation (CDGs) comprise a large number of inherited metabolic defects that affect the biosynthesis and attachment of glycans. CDGs manifest as a broad spectrum of disease, most often including neurodevelopmental and skeletal abnormalities and skin laxity. Two patients with biallelic CSGALNACT1 variants and a mild skeletal dysplasia have been described previously. We investigated two unrelated patients presenting with short stature with advanced bone age, facial dysmorphism, and mild language delay, in whom trio‐exome sequencing identified novel biallelic CSGALNACT1 variants: compound heterozygosity for c.1294G>T (p.Asp432Tyr) and the deletion of exon 4 that includes the start codon in one patient, and homozygosity for c.791A>G (p.Asn264Ser) in the other patient. C SGALNACT1 encodes CSGalNAcT‐1, a key enzyme in the biosynthesis of sulfated glycosaminoglycans chondroitin and dermatan sulfate. Biochemical studies demonstrated significantly reduced CSGalNAcT‐1 activity of the novel missense variants, as reported previously for the p.Pro384Arg variant. Altered levels of chondroitin, dermatan, and heparan sulfate moieties were observed in patients' fibroblasts compared to controls. Our data indicate that biallelic loss‐of‐function mutations in CSGALNACT1 disturb glycosaminoglycan synthesis and cause a mild skeletal dysplasia with advanced bone age, CSGALNACT1‐CDG. Abstract : Congenital disorders of glycosylation (CDGs) comprise a large number of inherited metabolic defects that affect the biosynthesis and attachment of glycans. Four patients with biallelic CSGALNACT1 variants and a mild skeletal dysplasia are now known. Biallelic loss‐of‐function mutations in CSGALNACT1 disturb glycosaminoglycan synthesis and cause a mild skeletal dysplasia with advanced bone age, CSGALNACT1‐CDG